Buckwheat digestibility affected by the chemical and structural features of its main components. (November 2019) - Yang, Jie; Gu, Zhengbiao; Zhu, Ling; Cheng, Li; Li, Zhaofeng; Li, Caiming; Hong, Yan
Abstract: To understand the mechanisms of buckwheat digestion, in vitro and in vivo digestibility of buckwheat flour (BF), buckwheat starch (BS), defatted buckwheat flour (DFBF), and deproteinized buckwheat flour (DPBF) were investigated. The results showed that fat and protein could inhibit the digestion of BS. The resistant starch content of DFBF was decreased from 4.21% to 0.83%, and slowly digestible starch content was increased from 0.66% to 8.16%, compared with BF. The in vivo digestibility results showed that DFBF or DPBF has a shorter glucose release time and higher hepatic glycogen content than BF. Scanning electron microscopy and thermodynamic properties analyses were combined to study the interaction of starch, fat, and protein of buckwheat. These results indicated that proteins could wrap around the starch granules and limit the enzymolysis of starch. Fat-starch complex limited starch hydrolysis. This study could give good guidance for making new health care products. Graphical abstract: Image 10960 Highlights: Four kinds of buckwheat samples were prepared by a gradual separation method. Fat and protein could inhibit the digestion of buckwheat starch. Proteins could wrap around buckwheat starch and limited its enzymolysis. This fat-starch composite structure limits the middle phase of starch hydrolysis.